Sticky wages in a world of ideas - Kevin X. D. Huang; Munechika Katayama; Mototsugu Shintani; Takayuki Tsuruga (Osaka University, Institute of Social and Economic Research (ISER), 2022)
The search for new ideas by profit-seeking firms and knowledge spillovers are well-known and fundamental sources of modern economic growth. This paper examines the implications of idea production and knowledge capital for monetary business cycles. We construct a sticky-wage model where workers produce goods based on firm-specific knowledge capital and researchers develop new ideas aided by the economywide stock of knowledge. As a quantitatively small group in the economy, researchers are inconsequential for the real effects of monetary shocks when the returns to research are low. However, this intuitive conclusion can be overturned when the returns to research are high. In this situation, monetary shocks can have significant real effects as long as wages are sticky for researchers, even if wages are perfectly exible for workers, who are quantitatively dominant in the economy.
Keywords: E22; E24; E31; E52; 330; Ideas; nonrivalry; knowledge capital; sticky wages; monetary neutrality